PERANCANGAN GAME EDUKASI BELAJAR BAHASA INGGRIS BASIC UNTUK ANAK USIA DINI - Rizki Fatullah; Syaechurodji Syaechurodji (Teknik Informatika Fakultas Ilmu Komputer, 2019)
English is an international language that is taught and used in various countries in the world. English is one of the capital to enter the era of globalization, because this is the teaching of English at an early age must be done to prepare to compete in the current era of globalization. but in terms of teaching English to early childhood there are obstacles that children sometimes get bored and lazy when learning English. The design of this application is based on Android mobile in order to facilitate learning. The purpose of designing this application is so that children do not get bored learning English and have an interest in learning English, other than that to direct the habits of children playing games to be children who prefer to learn English.